A “Partnership” for the Professional Development of Librarian Researchers - Pamela Carson; April Lynn Colosimo; Michelle Lake; Brian McMillan (Partnership: The Canadian Journal of Library and Information Practice and Research, 2014)
In this article the authors introduce the Librarians’ Research Partnership (LRP), founded in 2013, at McGill and Concordia University Libraries. The Partnership was inspired by the Canadian Association of Research Libraries’ Librarians’ Research Institute (CARL LRI) which was attended by three of the authors in 2012 and is described here from the point of view of the participants. The authors touch upon the research culture at McGill and Concordia Libraries and discuss barriers and supports for research as prominent themes in the literature on the research role of Canadian academic librarians. The formation of the LRP and the eight subsequent meetings are explained in detail, as well as the factors that made the LRP a successful initiative between the two universities: physical proximity, similarity of working environments, and common organizational culture. The article also includes a discussion of how the LRP’s philosophy might diverge from that of the LRI.